ANALISIS MANFAAT EKONOMI DAN LINGKUNGAN PENGGUNAAN PESTISIDA ORGANIK (KASUS PADA USAHA TANI PADI SAWAH DI KECAMATAN CLUWAK KABUPATEN PATI) - Agustono Agustono; Catur TBJP; Imammudin Syah (Universitas Sebelas Maret, 2004)
This research aims (1) to know benefit of organic fertilizer looking at from productivity and saving cost of ricefield farming; (2) to know economic and environment benefit used to organic fertilizer for community. the result of this research show used of organic fertilizer will give benefit saving cost is 30,3% and productivity improvement is 11,6% and for involved side off-farm activity will get insentive 58,1% from total benefit